Nursing interventions for substance use during psychiatric hospital admissions: Clinical context and predictors. (23rd August 2015) - Stewart, Duncan; Warren, Jonathan; Odubanwo, Adewunmi; Bowers, Len
Abstract: Empirical information about how nurses manage substance use on psychiatric wards is lacking. The aims of the study were to identify the frequency and clinical features of incidents among a sample of inpatients over a 12‐month period and how nursing staff intervened. Electronic, anonymized inpatient records were searched for incidents of substance use on 17 acute psychiatric wards in four hospitals in London. Searches were conducted for all patients admitted during 2012 and details of incidents and patient characteristics were extracted for analysis. Substance use was reported for 291 patients, with 25 incidents per 100 patients admitted to hospital. Only half of the incidents were followed by a response that specifically addressed the patients' substance use behaviour. These interactions usually concerned the circumstances and reasons for use, but rarely involved specific support for patients' substance use problems. The likelihood of staff taking any form of action was increased if the patient had been formally admitted, and was reduced if the patient was subject to containment during the shift or had a history of self‐harm. The results demonstrate that nurses require specific training and guidance on supporting substance using patients.